Outcomes after cryoballoon ablation of paroxysmal atrial fibrillation with the PolarX or the Arctic Front Advance Pro: a prospective multicentre experience. Issue 3 (24th January 2023) - Tanese, Nikita; Almorad, Alexandre; Pannone, Luigi; Defaye, Pascal; Jacob, Sophie; Kilani, Mouna Ben; Chierchia, Gianbattista; Venier, Sandrine; Cardin, Christèle; Jacon, Peggy; Combes, Stéphane; Deschamps, Elodie; et al.
Abstract: Aims: The aim of this study was to compare procedural efficacy and safety, including 1-year freedom from AF recurrence, between the novel cryoballoon system PolarX (Boston Scientific) and the Arctic Front Advance Pro (AFA-Pro) (Medtronic), in patients with paroxysmal AF undergoing PVI. Methods and results: This multicentre prospective observational study included 267 consecutive patients undergoing a first cryoablation procedure for paroxysmal AF (137 PolarX, 130 AFA-Pro). Kaplan-Meier curves with the log-rank test was used to compare the 1-year freedom from AF recurrence between both groups. Multivariate Cox model was performed to evaluate whether the type of procedure (PolarX vs. AFA-Pro) had an impact on the occurrence of AF recurrences after adjustment on potentially confounding factors. The PolarX reaches lower temperatures than the AFA-Pro (LSPV 52 ± 5, vs. 59 ± 6; LIPV 49 ± 6 vs. 56 ± 6; right superior pulmonary vein: 49 ± 6 vs. 57 ± 7; right inferior pulmonary vein: 52 ± 6 vs. 59 ± 6; P < 0.0001). A higher rate of transient phrenic nerve palsy was found in patients treated with the PolarX system (15% vs. 7%, P = 0.05). After a mean follow-up of 15 ± 5 months, 20 patients (15%) had recurrences in AFA-Pro group and 27 patients (19%) in PolarX group ( P = 0.35). Based on survival analysis, no significant difference was observed between both groups with a 12-month free of recurrence survival of 91.2% (85.1–95.4%) vs. 83.7% (76.0%–89.1%) (log-rank test P = 0.11). In multivariate Cox model hazard ratio of recurrence for PolarX vs. AFA-Pro was not significant [HR = 1.6 (0.9–2.8), P = 0.12]. Conclusion: PolarX and AFA-Pro have comparable efficacy and safety profiles for pulmonary veins isolation in paroxysmal atrial fibrillation. Abstract : The study compared procedural efficacy and safety, and the 12 months AF recurrence, between the PolarX, a new cryoballoon recently available, and the AFA-Pro. We considered 267 consecutive patients undergoing a first cryoablation procedure for paroxysmal AF (137 PolarX, 130 AFA-Pro). The PolarX cryoballoon reaches lower temperatures than the AFA-Pro. A higher rate of transient phrenic nerve palsy was found in patients treated with the PolarX system. No significative differences have been showed in term of 1-year freedom of AF recurrences between the two cryoballoon systems.